Limiting absorbing belt for a quasiperiodically driven mapping of the shift of intervals - Teplins’kyi, O. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
For a discontinuous dynamical system with discrete time on a two-dimensional cylinder generated by a quasiperiodically driven mapping of the shift of intervals with overlapping, we prove the existence and uniqueness of a limiting semiinvariant absorbing belt whose width lies within the same limits as the width of overlapping. In the case of overlapping of constant width, this belt is invariant, and the dynamics inside the belt is equivalent to a skew shift on a two-dimensional torus.